Value of auto-exam to evaluate cure of bacterial vaginosis - Orsini, Adrián; Osuna, Matías Santomé; Cuevas, Carlos A. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: bacterial vaginosis is the most prevalent infection of the lower genital tract in women in reproductive age being associated with obstetric and gynecological complications and increased risk of acquiring sexually transmitted infections. The etiology is polymicrobial (GAMM complex) used for diagnosis at least three of the four Amsel criteria. Objetive: self examination by the patient is a beneficial factor to consider the cure after antimicrobial therapy. Methods: 378 symptomatic patients were evaluated using the Amsel criteria wich were referred to the office of infections in gynecology of the OSPM. We used metronidazole 500 mg every 12 hs for 7 days and interviewed the patients four weeks later to assess the subjectivity of clinical cure and other microbiological research. Results: the results were that 77,89% of the patients said to have been cured (77,16% had normal microbiota, 9,69% bacterial vaginosis, 13,15% other pathology) while 22,11% did not report any improvement, or were biased, or the disease returned after treatment (48,78% normal microbiota, 26,83% bacterial vaginosis and 24,39% other pathology). The sensitivity of self examination was 44%, specificity 84%, PPV of 35% and NPV of 88%. Conclusion: the present study demonstrates the usefulness of the routine flow study in all patients complaining of vaginal discharge according to the Amsel criteria. Since bacterial vaginosis is associated with multiple complications, we consider it necessary to make a correct diagnosis based on easily reproductible criteria and methods to make an appropriate treatment of our patients.